The Collaborative Ocular Tuberculosis Study (COTS) Consensus (CON) Group Meeting Proceedings. (30th September 2020) - Agrawal, Rupesh; Testi, Ilaria; Mahajan, Sarakshi; Yuen, Yew Sen; Agarwal, Aniruddha; Rousselot, Andres; Raje, Dhananjay; Gunasekeran, Dinesh Visva; Kon, Onn Min; Barisani-Asenbauer, Talin; Kempen, John H.; Gupta, Amod; et al.
ABSTRACT: An international, expert led consensus initiative was set up by the Collaborative Ocular Tuberculosis Study (COTS) group to develop systematic, evidence, and experience-based recommendations for the treatment of ocular TB using a modified Delphi technique process. In the first round of Delphi, the group identified clinical scenarios pertinent to ocular TB based on five clinical phenotypes (anterior uveitis, intermediate uveitis, choroiditis, retinal vasculitis, and panuveitis). Using an interactive online questionnaires, guided by background knowledge from published literature, 486 consensus statements for initiating ATT were generated and deliberated amongst 81 global uveitis experts. The median score of five was considered reaching consensus for initiating ATT. The median score of four was tabled for deliberation through Delphi round 2 in a face-to-face meeting. This report describes the methodology adopted and followed through the consensus process, which help elucidate the guidelines for initiating ATT in patients with choroidal TB.